Aurantimycin resistance genes contribute to survival of Listeria monocytogenes during life in the environment. Issue 4 (27th February 2019) - Hauf, Samuel; Herrmann, Jennifer; Miethke, Marcus; Gibhardt, Johannes; Commichau, Fabian M.; Müller, Rolf; Fuchs, Stephan; Halbedel, Sven
Summary: Bacteria can cope with toxic compounds such as antibiotics by inducing genes for their detoxification. A common detoxification strategy is compound excretion by ATP‐binding cassette (ABC) transporters, which are synthesized upon compound contact. We previously identified the multidrug resistance ABC transporter LieAB in Listeria monocytogenes, a Gram‐positive bacterium that occurs ubiquitously in the environment, but also causes severe infections in humans upon ingestion. Expression of the lieAB genes is strongly induced in cells lacking the PadR‐type transcriptional repressor LftR, but compounds leading to relief of this repression in wild‐type cells were not known. Using RNA‐Seq and promoter‐ lacZ fusions, we demonstrate highly specific repression of the lieAB and lftRS promoters through LftR. Screening of a natural compound library yielded the depsipeptide aurantimycin A – synthesized by the soil‐dwelling Streptomyces aurantiacus – as the first known naturally occurring inducer of lieAB expression. Genetic and phenotypic experiments concordantly show that aurantimycin A is a substrate of the LieAB transporter and thus, lftRS and lieAB represent the first known genetic module conferring and regulating aurantimycin A resistance. Collectively, these genes may support the survival of L. monocytogenes when it comes into contact with antibiotic‐producing bacteria in the soil. Abstract : Listeria monocytogenes is a soil bacterium that can infect humans upon ingestion. Numerous genes are known that are specifically expressed during infection, but less is known about genes important for survival in the soil. We identified the first genetic module regulating and mediating resistance against the depsipeptide antibiotic aurantimycin A. This substance is produced by Streptomyces species sharing the soil habitat. Consequently, these genes may support survival of an important human pathogen in its natural reservoir.